Analysis of Intrinsic Motivation and Organizational Culture on the Performance of Military Court Employees I-02 Medan - Sarifah Aini Kembaren; Rahmat Daim Harahap (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of intrinsic motivation on the performance behavior of the employees of the Military Court I-02 Medan and analyze organizational culture on the performance of the employees of the Military Court I-02 Medan. The method I use is descriptive qualitative method. The subject of this research by way of interviews. The results showed that intrinsic motivation and organizational culture partially had a positive and significant effect on employee performance at the Military Court I-02 Medan